Covid-19 and its quarantine impact on psychological phenomena`s: exercise addiction and sport commitment of elite athletes - Ghabel Damirchi, B.; Khanjani, G.; Dabbagh, H.; Gharayagh Zandi, H. (Journal of Motor and Behavioral Sciences, 2020)
Introduction & Purpose: The present study aimed at investigating the relationship between exercise addiction and sport commitment of athletes and closure of sports venues and events due to corona virus (Covid-19). Methodology: The current study was a descriptive correlational one. The participants of the study consisted of 134 elite athletes (64 men) who had at least 5 years of sports experience at the level of the super league and national with an average age of 20.87 (15 to 35 years). To measure Sport Commitment, Sport Commitment Questionnaire of Scanlan et al. has been applied, and Terry et al.`s exercise addiction checklist has been used to measure the exercise addiction. The collected data has been analyzed by means of Spearman's correlation coefficient and regression. Results: The results of the study revealed a significant positive relationship between sport commitment and components of sport commitment and enjoyment, social constraints and personal investment with exercise addiction. In addition, sport commitment and its components explain 29% of the variability of exercise addiction scores. Besides, personal investment significantly predicted exercise addiction (p < 0.05). Conclusions: According to the findings, during due to Covid-19, with decreasing sport commitment, exercise addiction of athletes will be increased. Moreover, personal investment was also a good predictor of exercise addiction.